In Vitro Efficacy of Antiviral Agents against Omicron Subvariant BA.4.6 - Takashita, Emi; Yamayoshi, Seiya; Halfmann, Peter; Wilson, Nancy; Ries, Hunter; Richardson, Alex; Bobholz, Max; Vuyk, William; Maddox, Robert; Baker, David A.; Friedrich, Thomas C.; O’Connor, David H.; et al. (The New England journal of medicine, 2022)
Efficacy of Antiviral Agents against Omicron BA.4.6Researchers report that antiviral agents remdesivir, molnupiravir, and nirmatrelvir and monoclonal antibodies bebtelovimab and imdevimab retain effectiveness against the BA.4.6 subvariant in vitro.